Biomechanical Analysis of Knotless Flexor Tendon Repair Using Large-Diameter Unidirection Barbed Suture. (September 2013) - Lin, Toni E.; Lakhiani, Chrisovalantis; Lee, Michael R.; Saint-Cyr, Michel; Sammer, Douglas M.
Purpose: In traditional flexor tendon repairs, suture knots can be sites of weakness, impair tendon healing, stimulate an inflammatory response, and increase the bulk of the tendon repair. Because of this, there has been an increased interest in knotless flexor tendon repair using barbed suture. Since knots are not required, it may be possible to increase the strength of the tendon repair by using a large-diameter barbed suture. The purpose of this study was to biomechanically compare a traditional four-strand tendon repair using 3–0 braided polyester with a similar knotless four-strand tendon repair using 0 unidirectional barbed suture. Methods: Twenty-two matched cadaveric flexor digitorum profundus tendons were lacerated and assigned to repair by a four-strand modified Kirchmayr–Kessler technique using 3–0 braided polyester ( n =11) or knotless four-strand modified Kirchmayr–Kessler repair using 0 unidirectional barbed suture ( n =11). Repaired tendons were linearly distracted to failure at 20 mm/min after 1 N preload. Maximum load and load at 2-mm gap formation were recorded. Maximum load and load at 2-mm gap formation were compared with the Student's t test, and p values≤0.05 were considered significant. Results: The mean maximum load of the barbed, knotless suture repair was higher than that of the traditional repair (52 vs. 42 N). There was no difference between the two groups in the mean load required to produce a 2-mm gap. Conclusions: The four-strand knotless tendon repairs using a large-diameter unidirectional barbed suture were stronger than the traditional four-strand repairs using 3-0 braided polyester, and had similar 2-mm gap resistance.